LAYANAN BIMBINGAN KLASIKAL TENTANG MOTIVASI BELAJAR PESERTA DIDIK KELAS XI IPS SMA NEGERI 2PONTIANAK - Marini Nurul Hidayah E E; Purwanti Purwanti; Sri Lestari (Universitas Tanjungpura, 2019)
AbstractQuality education is not enough only through the science of education and technology alone, for that guidance and counseling is tasked with assisting the acquisition of science and technology through education. One service that can be given to students to achieve optimal development in accordance with their potential was classical guidance services. Guidance and counseling services that can help maintain and increase learning motivation, namely classical guidance services because classical guidance activities can help students to get a lot of information from counselors that can be used to help solve problems faced, especially in improving student achievement. A common problem in this study was